How Effective Social Marketing Approach Used in Promoting Behavior Changes – The Prevention of Corona Virus Transmission (COVID-19) In Indonesia - Nurjanah, Siti; Iskandar, Donant Alananto; Sumbogo, Ignatius Ario (TOPAZART, 2024)
This study aims to determine the extent to which social campaigns affect the level of acceptance of the Indonesian people towards social distancing behavior, using masks, washing your hands in 20 seconds and no handshake when greeting someone - as positive social behavior towards social welfare. In addition, this study also aims to determine the effectiveness of the level of public acceptance of the occurrence of voluntary social behavior as promoted by the government. This study uses a quantitative approach. Respondents in this study were Indonesian people. The grouping for the object under study includes public service places, places of worship, workplaces, malls, traditional markets. The results of this study indicate that Social Marketing has a positive and significant effect on Social Behavior. Social Marketing has a negative effect on Public Acceptance. Social Marketing has a positive and significant effect on Public Acceptance.